Reactivation of an Intraplate Fault by Mine‐Blasting Events: Implications to Regional Seismic Hazard in Western Canada. Issue 6 (14th June 2020) - Dokht, Ramin M. H.; Smith, Brindley; Kao, Honn; Visser, Ryan; Hutchinson, Jesse
Abstract: Mining activities are well known for being able to induce local seismicity but have not yet been shown to cause earthquakes over large distances. We analyze a particular group of seismic events recorded from 2014 to 2016 in north‐central British Columbia (BC) that appear to be triggered by the activities at the Mount Milligan Mine. The spatial distribution of the studied events follows a NW‐SE linear trend, with distances up to approximately 100 km from the mining site. To distinguish mining blasts from blasting‐related and natural events, we adopt a multivariate decision tree based on each event's origin time, distance from the mine, and the pseudo‐spectral acceleration ratios of the three‐component waveforms. The calculated dynamic strains from blasts place a distance limit of 20 km for dynamic triggering. However, accounting for the estimated epicentral uncertainty and temporal distribution of the earthquakes' origin times support the existence of blasting‐triggered events at larger distances (up to ∼50 km) from the mine, suggesting that a previously unmapped fault segment is close to critical state and may have been reactivated. The inferred fault segment aligns remarkably well with the southern extent of the Rocky Mountain Trench and may impose a significant hazard to nearby communities if the entire fault segment of about 150 km‐long ruptures. Key Points: Possibility of an event being triggered by blasts is determined by analyzing its spatio‐temporal occurrence and spectral characteristics Epicenters of blasting‐induced events suggest the presence of an unmapped NW‐SE trending fault reactivated by repeating mining explosions The inferred fault segment, a split branch of the Rocky Mountain Trench fault system, can generate an earthquake of magnitude up to MW 7.6